Influence of polymorphism of the gene of inducible NO-synthase on the achievement of control of bronchial asthma in children against the background of inhalation corticosteroid therapy - I. Yu. Smirnova; I. V. Petrova; I. A. Deyev (Бюллетень сибирской медицины)
The polymorphism of the gene of inducible NO-synthase (iNOS) was studied in 65 children with bronchial asthma (BA). The goal was to determine the probability to achieve the BA control in children against the background of inhalation glucocorticosteroid (IGCS) therapy depending on the polymorphism of the iNOS gene. The genotype of polymorphism of the iNOS gene was studied by the method of polymerase chain reaction. It has been found that the achievement of BA control in children against the background of the IGCS treatment is associated with the carriage of homozygote of «wild» allele G of polymorphism G954C of the iNOS gene. The absence of BA control is related to the presence of pathological allele . The result obtained can favor the pre С - diction of the uncontrollable BA course in children.